Food, consumption, and the body in contemporary women's fiction - Sceats, Sarah (Cambridge University Press, 2000)
"This study explores the subtle and complex significance of food and eating in contemporary women's fiction. Sarah Sceats reveals how preoccupations with food, its consumption and the body are central to the work of writers such as Doris Lessing, Angela Carter, Margaret Atwood and others. Through close analysis of their fiction, Sceats examines the multiple metaphors associated with these themes, making powerful connections between food and love, motherhood, sexual desire, self-identity and social behaviour."--Jacket